2012
DOI: 10.1111/jfpe.12006
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Assisted Infrared Drying of Pear Slices: Textural Issues

Abstract: The aim of this research was to investigate the impact of high‐intensity ultrasound as pretreatment on the duration of drying and texture characteristics of infrared‐dried pear slices using different amplitudes. Ultrasound device with a power capacity of 400 W, working at a frequency of 24 kHz and amplitudes of 25, 50, 75 and 100%, was used for pretreatment. Drying was performed in an infrared dryer at 70C. The results obtained showed how application of ultrasound with various amplitudes influenced the shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 33 publications
1
29
0
2
Order By: Relevance
“…5 Studying the extraction time (20,30, 40 min), it was observed that the mass fraction of the extracted phenols slightly Content of phenolic acids and flavone glycosides are expressed as mg per 100 g of dry sage; the sum of hydroxycinnamic acids (caffeic acid, salvianolic K and I acids, methyl rosmarinat); the sum of hydroxybenzoic acids (vanillic and syringic acids); Luteolin glycosides (6-hydroxyluteolin-7-glucoside, luteolin-7-glucuronide, luteolin-7-glucoside, luteolin-3-glucuronide); Apigenin glycosides (apigenin-7-glucuronide, apigenin-7-glucoside).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Studying the extraction time (20,30, 40 min), it was observed that the mass fraction of the extracted phenols slightly Content of phenolic acids and flavone glycosides are expressed as mg per 100 g of dry sage; the sum of hydroxycinnamic acids (caffeic acid, salvianolic K and I acids, methyl rosmarinat); the sum of hydroxybenzoic acids (vanillic and syringic acids); Luteolin glycosides (6-hydroxyluteolin-7-glucoside, luteolin-7-glucuronide, luteolin-7-glucoside, luteolin-3-glucuronide); Apigenin glycosides (apigenin-7-glucuronide, apigenin-7-glucoside).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency (kHz), amplitude (%), applied cycle (%), nominal output power (W), and geometrical parameters of the sonotrode (length and diameter -mm) should be carefully prepared and taken into consideration. [20][21][22] The choice of method for the extraction of polyphenols from sage depends on the type of compounds to be extracted, and is found to be dependent on the solvent employed. From literature data, 3 extraction of polyphenols using polar solvents is significantly improved by sonication.…”
Section: Comparison Of Conventional and Ultrasound-assisted Extractiomentioning
confidence: 99%
“…As a result of such propagation, alternating high pressure, cycles that cause compression of the cavitational bubbles, and low pressure that causes rarefaction of the cavitational bubbles occur. Within those bubbles, the conditions are possible to reach temperatures up to 5000 K and the pressures -a maximum of 50 MPa (Brnčić et al, 2010;Dujmić et al, 2013;Lagnika et al, 2014). After numerous repeats of the cycles, cavitational bubbles implode and deliver their energy to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ultrasound on proteins prior to enzymatic hydrolysis may improve the release of bioactive peptides due to the protein unfolding and enhanced accessibility of enzymes; however, it is influenced by the protein purity and structure [14,15]. Ultrasonic pretreatment as a nonthermal process for the modification of food ingredients has attracted more attention in the development of new, gentle processes to get better quality and safety of processed foods [16,17]. Principally sonication acts by producing bubble cavitation in the biological medium.…”
Section: Introductionmentioning
confidence: 99%